EXPLORE BUSINESS OPPORTUNITYS IN THE SPORT INDUSTRY IN BEKASI: WEB-BASED FUTSAL FIELD RENT INFORMATION SYSTEM - Ferry Kurniawan; Achmad Fauzi; Ahmad Muchlisin Natas Pasaribu; Rizty Dwi Nurazizah; Alfath Nare Utama; Aditya Tri Syahbanu; Ade Ilham Prasetyo; Andhika Rifki Prasetyo; Bagus Naufal Putra Shawa (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
The nation's economic development and the sports sector both depend on the sports industry. Offers field rental for sports, especially futsal. Companies that rent out futsal courts are called "futsal field rentals". The expansion of futsal rental in a number of places, including Bekasi, shows the growing importance of rental in the company's economic potential. This software will be ordered by the information system in an effort to help with the futsal field rental problem. To be useful, futsal field rentals currently utilize software-based technology (website). With the hope of reaching all the people who still rent by hand. This study aims to determine the potential value of business in the sports sector in projecting online futsal field rentals based on the results of information systems via the website. This study uses qualitative methods with journals for literature review.